Human-in-the-Loop Control: Applications and Categorization. Issue 5 (2020) - Samad, Tariq
Abstract: I review the variety of human-in-the-loop control systems, identifying four architectural templates for the field: human-in-the-plant, human-in-the-controller, human-machine control symbiosis, and humans-in-control-loops. Examples from numerous application sectors are used to illustrate the concepts and their evolution. A timeline of developments is presented. The paper concludes with a few suggestions, both taxonomic and technical, for future work.